Effect of addition of erbium stabilized bismuth oxide on the conductivity of lanthanum doped ceria solid electrolyte for IT-SOFCs - Jaiswal N.; Gupta B.; Kumar D.; Parkash O. (My University, 2025)
Nanosized powders of compositions, Bi0.8Er0.2O1.5 (ESB) and Ce0.85La0.15O1.925 (CLO) have been prepared using citrate-nitrate auto combustion method. ESB added CLO (ECLO) samples have been prepared by mixing nanosized CLO powder with 0.5, 1, 2 and 3 wt.% of ESB. X-ray diffraction patterns confirm that all the samples are single phase having cubic fluorite structure similar to CeO2. Density of Ce0.85La0.15O1.925 increases with increasing ESB content. All the samples have been sintered at 1350 °C. All the ECLO samples have density more than 97% of the theoretical value. Field emission scanning electron microscope images show dense microstructure with distinct grains and grain boundaries. Impedance measurements have been made in the temperature range 200-700 °C in air. Addition of ESB increases the conductivity of the bulk as well as of grain boundaries. Ce0.85La0.15O1.925 with 0.5 wt.% of ESB exhibits the maximum conductivity 1.41 × 10-2 S cm-1 at 600 °C of all the compositions. This value is one order of magnitude higher than the conductivity of Ce0.85La0.15O1.925 (1.99 × 10-3 S cm-1). © 2015 Elsevier B.V.